DISTANCE EDUCATION: FROM EARLY TECHNOLOGIES TO ONLINE COURSES (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
From its inception, distance education has changed with the tides of time and technological advancement. It moved from a correspondence course basis in the early days, where materials were printed, through the advent of radio, television, and ultimately, the internet. With the advent of modern digital platforms and online courses, the revolution in access to education has broken down barriers: geographical, financial, and temporal. The historical development of distance education is traced in this paper, from the very earliest technologies to the advent of online learning. This work considers the ways in which technological innovations-consider MOOCs, mobile learning, and AI-are influencing contemporary education. By considering these trends, this paper provides insight into the evolution of distance education and its potential for reshaping the future of learning around the world.